S-O-R ANALYSIS OF LIVE STREAMING PRODUCT PROMOTIONS TECHNOLOGY TOWARDS THE BUYING IMPULSES OF MUSLIM CONSUMERS - Nisa, Rachmadanti Chairatul (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction : Impulsive purchases are common, not only in physical stores but also in online stores, especially online buyers are found to be more impulsive than buyers who do not shop online Characterized by the growing growth of e-commerce. Live streaming of e-commerce is considered a trend and a new experience for consumers to shop. Live streaming shopping allows one to view, comment, and interact with sellers (streamer) online. Methods: This study is based on the SOR theory and develops factors that influence impulsive purchases after watching live streaming. This study aims to explore the impact of live streaming on impulsive consumer purchasing intentions. The Smart PLS program is used in conjunction with the data obtained through the questionnaire. Results: The analysis showed that influencer and convenience stimuli have a significant positive influence on perceived enjoyment in live streaming e commerce. Conclusion and suggestion: This research can be a reference for further research related to the influence of influencers, comfort, perceived enjoyment on impulsive purchasing intentions through live streaming e commerce.